The Life Cycle of Rules - Jackson, John H.; Adams, Susan W. (Academy of Management Review, 1979)
This article examines rules from the organizational perspective and also discusses their impact on organization members. The authors address three areas that are traditionally studied when examining rules, which are, rule making, rule adherence and rule deviation. In examining these areas the authors discuss how rules fulfill individual as well as organizational needs. They also suggest that rules serve the organization by reducing the variability of human behavior and by making it easier to predict the results of organizational activities. They examine instances where rule adherence is high as well as instances that lead to rule deviation. The authors suggest that deviation usually occurs when rules become outdated and a change in necessary.